Evaluating the summative effectiveness of a curriculum integrated STEM-based web research hub in fostering science literacy among junior high school students - Fikri Aulia; Affero Bin Ismail; Dadi Mulyadi; Rayendra Rayendra; Wikan Budi Utami (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
The need for holistic STEM learning innovations is crucial to enhance students’ scientific literacy in the digital era. This RnD study aims to develop a web-based Research Hub as a technology-rich learning environment and evaluate its empirical impact on students’ scientific literacy. Utilizing the Lee & Owens framework, the study adopted a one-group pretest-posttest design to evaluate its effectiveness. The sample consisted of ninth-grade students from a junior high school in Malang Raya subjected to a two week intervention. Data werw collected using a 20 item two tier scientific literacy test adapted to the PISA 2022 framework. Descriptive statistics showed a positive shift in the mean score from 63.65 at pretest to 72.13 at posttest, yielding a mean difference gain of 8.48. Prerequisite testing confirmed that the dataset was normally distributed. The subsequent parametric Paired Sample T-Test demonstrated a highly significant increase in scientific literacy with , , 2, with a 95% Confidence Interval ranging from -9.465 to -7.503. Furthermore, calculating the magnitude of the intervention yielded an exceptionally large Cohen’s d effect size , proving that the integrated Research Hub framework provides substantial empirical power in advancing student competencies compared to traditional platform limits. In conclusion, the technology-rich Research Hub is highly effective, valid, and scalable in improving junior high school students’ scientific literacy within modern STEM education frameworks.